Real-world eligibility and cost-effectiveness analysis for empagliflozin in patients with heart failure. (3rd October 2022) - Kim, E S; Park, S K; Youn, J C
Abstract: Background/Introduction: Empagliflozin was approved by the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) for reducing cardiovascular mortality and heart failure (HF) hospitalization in both patients with HF with reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF). Purpose: Limited data are available on the generalizability of empagliflozin to clinical practice. Therefore, we evaluated real-world eligibility and cost-effectiveness based on a nationwide prospective HF registry. Methods: For the study, 3108 HFrEF and 2070 HFpEF patients from the Korean Acute Heart Failure (KorAHF) registry were analysed. Eligibility was estimated by FDA and EMA label criteria and by inclusion and exclusion criteria of EMPEROR-Reduced and EMPEROR-Preserved trials. The cost-effectiveness analysis was performed using the decision tree model, where effectiveness was the avoidance of the first hospitalization. Results: Among the KorAHF patients, 91.4% met FDA & EMA label criteria, while 44.7% met the clinical trial criteria. The main factor for exclusion in the clinical trial-based empagliflozin eligibility was low systolic blood pressure, including 18.7% of HFrEF and 11.0% of HFpEF patients. Other factors were acute (<4 weeks) myocardial infarction and impaired renal function (eGFR <20 mL/min/1.73 m 2 or requiring dialysis). The overall expected hospitalization rate and cost reduction were 3.6 and US 14, 885 per 100 eligible HF patients per year. In HFrEF patients, hospitalization rate and cost reduction were 4.8 and US 28, 442. However, in HFpEF, the cost was increased by US 7, 576, while hospitalization reduction was 1.7. Conclusion(s): There is a large discrepancy of real-world eligibility for empagliflozin between FDA & EMA labels and clinical trial criteria. The cost-effectiveness benefit was more evident in patients with HFrEF than HFpEF. The efficacy and safety of empagliflozin in real-world patients should be further investigated for a broader range of clinical applications. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): This work was supported by the National Research Foundation of Korea (NRF) grant funded by the Minister of Science and Information and Communication Technologies (NRF-2021R1F1A1063430), by the Catholic Medical Center Research Foundation (2022), and by the Research of Korea Centers for Disease Control and Prevention (2010-E63003-00, 2011-E63002-00, 2012-E63005-00, 2013-E6300300, 2014-E63003-01, 2015-E63003-02, 2016-ER6303-00, and 2017-ER6303-01).